Identification of Genes Essential for Antibiotic-Induced Up-Regulation of Plasmid-Transfer-Genes in Cephalosporin Resistant Escherichia coli - Liu, Gang; Olsen, John Elmerdahl; Thomsen, Line Elnif (Frontiers in Microbiology, 2019)
Bacterial conjugation is one of the most important mechanisms for spread of antibiotic resistance among bacteria. We have previously demonstrated that cefotaxime (CTX) exposure up-regulates expression of Type-IV conjugation transfer genes, and that this leads to increased transfer of a blaCTX-M-1 encoding IncI1 resistance plasmid pTF2 in Escherichia coli. To elucidate the underlying mechanisms, a search for genes that are essential for the up-regulated expression of the transfer (tra) genes in the presence of CTX was undertaken. We constructed a reporter gene-fusion strain MG1655/pTF2 ∆traF::lacZ where the promoter region of the traF-gene of the plasmid pTF2 was fused with a lacZ on the native plasmid. Random mutagenesis mediated by Tn5 transposon was carried out in the strain, and seven genes were identified where insertion prevented CTX-induced up-regulation of traF (rfaH, yhiN, waaP, waaQ, gnd, pgl and ISEcp1). Site-specific mutagenesis was carried out, and for all seven mutants, gene deletions abolished the CTX induced up-regulation of traF, and the increased conjugation transfer of the plasmid in the presence of CTX was no longer observed. In addition, the deletion of the genes also abolished CTX induced expression of the blaCTX-M-1 gene. Our results suggested that through CTX induced induction of the identified genes, blaCTX-M-1 expression increased, which led to up-regulation of traF and plasmid transfer. These data reveal that a number of chromosomally encoded genes contribute to the antibiotic induced up-regulation of the conjugation machinery of plasmids, and such genes may be future targets to prevent antibiotic induced spread of resistance plasmids.